"Tamoxifen for residual NF-PitNETs: a Proof-of-Concept study integrating receptor profiling, pilot trial, and target pathway analysis" - Haydar Ali Tajuddin, Amalina; Rullah, Kamal; Isa, Nur Firdaus; Mohd Nasir, Mohd Hamzah; Uddin, Md Nazim; Omar, Ahmad Marzuki (Springer, 2025)
Background Non-functioning neuroendocrine pituitary neuroendocrine tumors (NF-PitNETs) pose a therapeutic challenge due to their hormonal inactivity, mass effects and limited medical treatment options for residual or recurrent disease. There is increasing evidence that the oestrogen receptor (ER) is involved in the pathogenesis of these tumours. In this study, the potential therapeutic role of tamoxifen, a selective ER modulator, was investigated.